Studi Implementasi Undang-undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan dalam Pelaksanaan Program e-KTP di Kabupaten Pati - Ilsta Masrukah; Ari Subowo; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The back ground of this electronic KTP program cause administrative management ofpopulatio is overlape and the high total population in Indonesia, many cases of double identity card so the government made on UU number 23 2006 about administration inhabitant to apply the parent population number for residents of Indonesia This research was conducted using descriptive qualitative research method. The location was focused in Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pati. The selection of informants using purposive sampling. Triangulation techniques used to test the quality of the obtained data. The implementation of this program observed through the implementation stages, goals accuracy, and program performance. Based on thesynthesis of Implementation Models of Mazmanian and Sabatier, as well Edward III the chosen decisive factors in the program implementation were a communication, resourses, dispotition,and bierocr structure.So far, the study implementation of enrollment electronic KTP program in Pati was not running well because there are still many shortcomings in the implementation stages, goals accuracy, and program performance. Determinantfactors in this program implementation can be motivating factor, but also has a potential to be a limiting factor. Recommendations are: (1) Need to increase the number of procurement of equipment in order to complete the recording (2) Enhance program enroolment mobile e-KTP in the villages in order to help complete the recording e- KTP (3) Provision of access to information and education program of electronic KTP card (4) Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pati shall supervise the implementation of the electronic KTP and equipment procurement program (5) the purpose of the e-ID card needs to be disseminated to the entire apparatus supporting this program.